Integrating Needs Analysis and Participatory Action Research to Develop English Textbook Material for Early Childhood Islamic Education - Amalia, Eka Rizki (Indonesian Journal of Early Childhood Education Studies, 2019)
English material in Early Childhood Islamic Education or Pendidikan Islam Anak Usia Dini (PIAUD) program have to fulfill the targeted competence specifically demanded by PIAUD program. The English given has to be be English for Specific Purpose (ESP). Unfortunately, the English material provided has not been prepared based on the needs of the PIAUD program. The preparation of ESP material must go through certain stages such as needs analysis that involve the subject as the basis for considering the preparation of the material. This concept is in accordance with the principles of Participatory Action Research (PAR) related to the subject participation. This research combines the model of needs analysis and PAR method. This is a Research and Development (R & D) model to develop an English module for PIAUD program. Interview and observation combined with survey are used as the instruments to collect the data. The steps of the whole process along with the discussion are presented. The result reveals that the English material is suggested to focus more on communication skill as the PIAUD students will later use it to teach. In addition, the method that is considered effective to teach the children has to be delivered on a daily basis and fun-based learning. Lastly, a suggestion for other researchers to conduct further research is proposed.